Reverse migration: The key for sustainable development in Uttarakhand - Singh, Sarita (Revista Review Index Journal of Multidisciplinary, 2024)
The formation of Uttarakhand as a separate state occurred in 2000, when it was separated from Uttar Pradesh to address the persistent developmental requirements and regional aspirations of its predominantly mountainous inhabitants. Migration outflows from Uttarakhand constitute a common occurrence, typically emerging as a consequence of the region's precarious resource foundation (encompassing land and forestry), environmental deterioration, and livelihood vulnerabilities. Migration is a process that has been ongoing since ages. People have been migrating in the world for different reasons in different period of time. Migration is an important issue that deserves serious attention of the people in general and the governments both central and state government in particular because no developmental schemes can succeed in a society absent of creative manpower. Tourism constitutes a fundamental pillar of Uttarakhand's economy, contributing substantially to the state's gross domestic product through diverse recreational and cultural activities.